Lean manufacturing based cloud enterprise resource planning for SME digitalization - Haekal, Jakfat (2023)
The Covid-19 pandemic is a right time for SME to grab the benefit of digital transformation. The SME that involved in digitalization will be more ready to deal with challenges of the pandemic. In current situation (2020-2022), the pandemic became a barrier to the face-to face business operations, resulting in a significant decrease of sales. A survey conducted by the Indonesian Chamber of Commerce and Industry (KADIN) in May 2020 found that around 70% of businesses in Indonesia had experienced a decline in sales due to the pandemic. Many businesses and organizations have had to rapidly adapt their operations and processes to comply with changing regulations, keep their employees safe, and meet the needs of their customers or clients. In order to overcome this issue, there is a motivation to find a more effective way of the digitalization framework. The purpose of this research is to develop a new framework of cloud enterprise resource planning (CERP) that is more effective for improving sales through a better productivity and low cost. The new CERP integrates business process re-engineering and lean manufacturing is able to digitalize the process at a minimum cost. The development process of the framework involves forum group discussions with seven expert including manager, director, and consultant. This framework has been implemented for one year in nine cosmetic companies showing the improvement in productivity by 77% through eliminating thirty one necessary non value-added activities (NNVA) and non value-added activities (NVA). The cost comparison shows that the proposed CERP framework has a lowest cost ($1001) compared to existing CERP softwares in the global market